Analisis Implementasi Bauran Promosi Dalam Meningkatkan Partisipasi Anggota Sebagai Pelanggan : Studi Kasus Pada Unit Niaga Kopkar PD. Kebersihan Kota Bandung “Dharma Nirmala” - Maryam, Siti; Darliah, Nais (Universitas Koperasi Indonesia, 2022)
The background of this research is the low participation of members in conducting transactions in commercial units, especially KDN Mart provided by cooperatives. This study to determine the application of the promotion mix at Kopkar PD Kebersihan Kota Bandung Dharma Nirmala, to determine the participation of members as customers of the and to find out what efforts can be made to increase the number of members. participation as a customer through the promotion mix. The research method used is descriptive analysis.The results of this study are involving 92 people, namely members of the cooperative as respondents to assess the implementation of the promotion mix. As for the results of this research, the promotion mix that is considered important for members and has been carried out well by the commercial unit needs to be maintained. Other indicators are advertisements, strategic ad places, advertising messages, ad designs and price discounts. The results of the research on member participation as customers, member participation in the Commercial Unit is still low and when viewed from the number of purchasing frequencies.